Perancangan Dashboard Evaluasi Pelaksanaan Kontrak Kerja dan Deadline Proyek di PT. X - Nicko Andrean (Jurnal Titra, 2022)
The construction industry has become one of the contributors to Indonesia's economic growth. A company has to hold on to the company's vision and mission and prioritize service for the customer. Therefore, the company needs to evaluate the performance of each department to give its best services to its customers. So far, the evaluations were done manually and without visualization. This work is answering the company needs, that is, designing a visualization dashboard that facilitates the evaluation of decision-making related to the achievement of departmental Key Performance Indicators (KPIs). The dashboard is designed for evaluating the implementation of work contracts and project deadlines, and monitoring the achievement of KPIs in the Finance/Accounting and Project department. It was designed using Power BI, a business intelligence software for constructing a powerful dashboard visualization. At the end of this work, the designed dashboard is able to simplify the evaluation of the decision-making process regarding each department's KPIs achievement.